Aesthetics in Quran and Sunnah of the Holy Prophet Muhammad (Pbuh) - Dr. Tahir Masood Qazi; Syed Haroon Gull Shah; Dr Hafiz Irfan Ullah; Bukhtiar Ahmed; Dr Hafiz Muhammad Hamid (Al-Qanṭara, 2024)
Allah Almighty is the creator of this marvelous universe which is a masterpiece of His artistic creation. Everything here in this universe glorifies Him with His praise in its own way and position. Having a thoughtful glance, we come to know that all these beautiful manifestations are the aesthetic signs of a glorious and dignified Creator. The concept of beauty (jamaal) is considered the intellectual foundation upon which many artistic achievements are built. This study aims to address the concept of beauty in Islam through two sources: The Noble Quran, the teachings and personality of the Prophet Muhammad(PBUH). A systematic literature review was conducted to collect data, and an analysis was performed to examine the topic of this study. Among the most important results is that the concept of beauty in Islam is divided into two parts: moral beauty and formal beauty. In Islamic vision, the former is more important than the latter. The Islamic understanding of certain concepts such as beauty may differ from the mainstream ones found in other civilizations due to differences in thought and belief. Some of these concepts have contributed to the formation of Islamic identity and, unconsciously, to the perception and behavior of Muslims (Che Man et al, 2016). The researcher believes that beauty took shape alongside the Islamic aesthetic view since Islamic civilization began to develop and follow the path of prosperity. The importance of talking about beauty (jamaal as a noun and jameel as an adjective in Arabic) is a key pillar of Islamic art. It is hoped that a clear conception of beauty according to the Islamic vision will produce positive results that can contribute to a deeper understanding of Islamic art. An inherent correlation exists between beauty as an idea and a vision, and the artistic or aesthetic achievement represented in all the results deriving from that understanding of beauty, which in turn reflects deep implications formed by a group of factors and influences (Hirsch, 2020). Therefore, this study explores the origins of the meaning of beauty (jamaal) and its connotations and the fields that are expected to be included or used within the Islamic concept.